Igneous Rock Associations 25. Pre-Pliocene Andean Magmatism in Chile - Oliveros, Veronica; Moreno-Yaeger, Pablo; Flores, Laura (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2020)
Andean-type magmatism and the term ‘andesite’ are often used as the norm for the results of subduction of oceanic lithosphere under a continent, and the typical rock formed. Although the Andes chain occupies the whole western margin of South America, the most comprehensively studied rocks occur in the present-day Chilean territory and are the focus of this paper. Andean magmatism in this region developed from the Rhaetian-Hettangian boundary (ca. 200 Ma) to the present and represents the activity of a long-lived continental magmatic arc. This paper discusses Pre-Pleistocene volcanic, plutonic, and volcano-sedimentary rocks related to the arc that cover most of the continental mass of Chile (between the Pacific coast and the High Andes) between the latitudes of 18° and 50°S. They comprise most of the range of sub-alkaline igneous rocks, from gabbro to monzogranite and from basalt to rhyolite, but are dominated by the tonalite-granodiorite and andesite example members. Variations in the petrographic characteristics, major and trace element composition and isotopic signature of the igneous rocks can be correlated to changes in the physical parameters of the subduction zone, such as dip angle of the subducting slab, convergence rate and angle of convergence. Early Andean magmatic products (Jurassic to Early Cretaceous) are found along the Coastal Cordillera in the westernmost part of the Andes. The rock record of the subsequent stages (Late Cretaceous, Paleocene–Early Eocene, Middle Eocene–Oligocene, Miocene) is progressively shifted to the east, reflecting migration of the magmatic front towards the continent. Tectonic segmentation of the convergent margin, as attested by the magmatic record, may have occurred throughout the Andean life span but it is particularly evident from the Eocene onwards, where the evolution of the northern part of the Chilean Andes (north of 27°S latitude) is very different to that of the southern segment (south of 27°S latitude).